A comparative analysis of serologic parameters and oxidative stress in osteoarthritis and rheumatoid arthritis: reply to Mishra and colleagues. - Girardelli, M; Bianco, A M; Marcuzzi, A; Crovella, S (Rheumatol Int, 2013)
In chronic diseases such as rheumatoid arthritis and osteoarthritis, the progression of the disease is characterized by stress oxidative, inflammation, and elevated levels of cholesterol. In mevalonate kinase deficiency, an auto-inflammatory disease, the correlation between inflammation and cholesterol levels is opposite. The metabolic pathway that underlies the production of cholesterol is the mevalonate pathway; it is also essential for the biosynthesis of isoprenoids involved in the control of several cell functions. This divergence of cholesterol levels, associated with these two inflammatory disorders, is probably due to a different etiology, pathogenesis, and progression.
Keywords: Arthritis, Rheumatoid; Female; Humans; Inflammation Mediators; Lipids; Male; Osteoarthritis; Oxidative Stress